Traceability in small claw-free graphs - Harris, John M.; Mossinghoff, Michael J. (Utilitas Mathematica, 2006)
We prove that a claw-free, 2-connected graph with fewer than 18 vertices is traceable, and we determine all non-traceable, claw-free, 2-connected graphs with exactly 18 vertices and a minimal number of edges. This complements a result of Matthews on Hamiltonian graphs.